Management and outcomes of neonates with down syndrome admitted to neonatal units. Issue 6 (June 2016) - Mann, Jake P.; Statnikov, Eugene; Modi, Neena; Johnson, Nik; Springett, Anna; Morris, Joan K.
Abstract : Background: Neonates with Down syndrome have an increased risk of being admitted to a neonatal unit compared with unaffected neonates. We aimed to estimate the proportion of neonates with Down syndrome admitted to a neonatal unit and compare their management and outcomes with other neonatal admissions. Methods: Case–control study of neonates born from 2009 to 2011 admitted to 122 NHS Neonatal Units in England using data from the National Down Syndrome Cytogenetic Register and the National Neonatal Research Database. For each neonate with Down syndrome, three neonates admitted to the same unit in the same month and born at the same gestation were identified. Results: Forty‐six percent of neonates with Down syndrome were admitted to a neonatal unit. Boys were more likely to be admitted than girls (odds ratio = 1.7; 95% confidence interval, 1.4–2.0). Neonates with Down syndrome required more intensive or high dependency care compared with unaffected neonates (37% vs. 27%. p < 0.01) and stayed in neonatal units for longer (11 days vs. 5 days, p < 0.01). A total of 31% of neonates with Down syndrome required respiratory support compared with 22% ( p < 0.001) of unaffected neonates, and 11% were discharged requiring oxygen supplementation compared with 3% ( p < 0.001) of unaffected neonates. A total of 3% of neonates with Down syndrome died in a neonatal unit compared with 1% ( p = 0.01) of unaffected neonates. Conclusion: Neonates with Down syndrome are more likely than unaffected neonates to be admitted to a neonatal unit, have a prolonged stay, and be discharged home on supplemental oxygen. Birth Defects Research (Part A) 106:468–474, 2016. © 2016 Wiley Periodicals, Inc.